Sustainable Development and Policies or Strategies Concerning Resources - Mirosława Czerny; Andrzej Czerny (Barometr Regionalny)
Since the 1990s the term (and underlying concept  ) of sustainable development has become the aspect arising most often in discussions regarding the Earth’s fate, the management of natural resources, energy policy, the safeguarding of food security and places to live, and so on. However, ideas on the accomplishment of sustainable development assumptions have first and foremost allowed for development and strengthening of all those ecological movements able to put political pressure on the governments of different countries, with a view to their devising and implementing policy on environmental protection, as well as the instrumentation allowing effective control over the exploitation of natural resources. Analyses concerning the structure and dynamics of contemporary use of natural resources for economic purposes which came into existence in time for the Rio “Earth Summit” (i.e., in the early 1990s) made it clear that the prevention of excessive change in the natural environment – and the guaranteeing of its appropriate quality for both present and future generations would be best served if the main focus was on raw materials and their use. This rather one-sided way of thinking did in fact evolve over time, to the point where activity in the name of sustainable development has now become multifaceted, involving a wide range of entities, and extending far beyond the field of raw-materials and resources use.